2017
DOI: 10.4081/jae.2017.677
|View full text |Cite
|
Sign up to set email alerts
|

Improving building energy modelling by applying advanced 3D surveying techniques on agri-food facilities

Abstract: Food industry is the production sector with the highest energy consumption. In Europe, the energy used to produce food accounts for 26% of total energy consumption. Over 28% is used in industrial processes. Recently, European food companies have increased their efforts to make their production processes more sustainable, also by giving preference to the use of renewable energy sources. In Italy, the total energy consumption in agriculture and food sectors decreased between 2013 and 2014, passing from 16.79 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…On the first floor ( Figure 5) there are the offices and there is also a large unit area (1400 square meters) for the storage of packaging, which is connected to the ground floor by a lift. The external walls, thick 12 cm, are made of concrete insulated panels, the indoor partition walls are made of plasterboard, while the refrigerating room walls are made of insulated aluminum sandwich panels [24]. On the first floor ( Figure 5) there are the offices and there is also a large unit area (1400 square meters) for the storage of packaging, which is connected to the ground floor by a lift.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the first floor ( Figure 5) there are the offices and there is also a large unit area (1400 square meters) for the storage of packaging, which is connected to the ground floor by a lift. The external walls, thick 12 cm, are made of concrete insulated panels, the indoor partition walls are made of plasterboard, while the refrigerating room walls are made of insulated aluminum sandwich panels [24]. On the first floor ( Figure 5) there are the offices and there is also a large unit area (1400 square meters) for the storage of packaging, which is connected to the ground floor by a lift.…”
Section: Resultsmentioning
confidence: 99%
“…On the roof of the building, a 1000 square meters of photovoltaic panels have been installed to The external walls, thick 12 cm, are made of concrete insulated panels, the indoor partition walls are made of plasterboard, while the refrigerating room walls are made of insulated aluminum sandwich panels [24].…”
Section: Resultsmentioning
confidence: 99%
“…A weather station was placed close to the building to survey the meteorological data ( Figure 6b). All the data surveyed by the sensor network were recorded at a time interval of 15 min by a data logger [22]. The surveyed data showed that, during the monitoring period, the temperature in the oil storage area was sometimes above 30 • C, a value far higher than the maximum correct temperature for the proper storage of extra-virgin olive oil.…”
Section: The Olive Oil Mill Buildingmentioning
confidence: 99%
“…The modelling and analysis carried out with such a software program allowed simulation and verification, in real-time, of the effectiveness of certain solutions. The developed model of analysis was calibrated by comparing the instrumental thermo-hygrometric measurements taken on site and the values obtained from the simulation under real conditions [21]. A few minor sustainable insulation interventions were proposed, such as the installation of a sun screen on the external wall exposed to the south-west; the separation of the storage area from the processing area by means of an internal mobile partition wall [22]; an automatic forced ventilation system with a 7 vol/h air renewal; the thermal insulation of the walls of the storage area with 7 cm-thick agglomerate cork boards (λ = 0.04 W·m −1 ·K −1 ) [23,24]; a better insulation and ventilation of the roof; and the construction of a Canadian well, i.e., a geothermal system that uses the energy present in the ground, just beneath the Earth's surface, to heat or cool ventilation air inside the buildings [25].…”
Section: Intervention Plansmentioning
confidence: 99%
“…The modelling and analysis carried out with such a software program allowed simulation and verification, in real-time, of the effectiveness of certain solutions. The developed model of analysis was calibrated by comparing the instrumental thermo-hygrometric measurements taken on site and the values obtained from the simulation under real conditions [21]. The instrumental analysis was carried out from 19 July to 29 September 2016, a time interval generally including the hottest period of the year [19].…”
Section: Intervention Plansmentioning
confidence: 99%